The Relationship Between Physical Activity and Mental Health in Middle School Students - Harri Romadhona; Zulfairah Zulfairah (Siber Nusantara Review, 2023)
The Relationship Between Physical Activity and Mental Health in High School Students is a scientific article of literature study in the scope of education and health. The purpose of this article is to build a hypothesis that physical activity plays a role in improving the mental health of high school students. The research objects come from online libraries such as Google Scholar, Mendeley, and other online academic media. The method used is library research sourced from e-books and open access e-journals. The analysis was carried out descriptively qualitatively. The results of this article show that: (1) Physical activity plays a role in high school students, and (2) Mental health plays a role in high school students.